INFLUENCE OF PARTICLE SIZE ON REDUCTION KINETICS OF NATURAL LATERITIC IRON ORES - M. Anis; Basso D. Makahanap; A. Manaf (Jurnal Sains Materi Indonesia, 2011)
INFLUENCE OF PARTICLE SIZE ON REDUCTION KINETICS OFNATURAL LATERITIC IRON ORES. This work is to report a laboratory investigation on the influence of particle sizes on reduction behavior of natural lateritic iron ore with anthracite coal under isothermal condition. The main minerals content of investigated ore were goethite = 62.8%, hematite = 18.3% and magnetite (Fe3O) = 6.2% and other oxide minerals like alumina = 6.6%, silica = 4.5%, chromate = 3.3% and others. The ore and anthracite coal of -100, -200 and -500 μm size with mol ratio between iron oxide and carbon in the anthracite of 1 : 1.88 were mixed, pressed into a composite of 12 mm diameter and 20 mm long and heated isothermally at four different temperatures for various reduction times. The metallization is determined by the reduction temperature and time. Mostly, effective reduction temperatures were found to be 1100 o 4 C resulted in the highest value of metallization of almost 96 %. The particle size seems has no significant influence on the metallization value at this reduction temperature. However, particle sizes influenced significantly the metallization for reduction temperatures of less than 1100 C from which values of metallization increased with decreasing in particle sizes.